Bankruptcies during Covid-19 in Italy: An interrupted time-series analysis - Valentina Ferri; Giovanni Gallo; Sergio Scicchitano (Global Labor Organization (GLO), 2025)
The COVID-19 pandemic triggered widespread economic disruptions, raising concerns about surging bankruptcy rates globally. Italy, one of the hardest-hit countries, faced significant risks of business insolvency. This paper empirically investigates the short-term impact of government interventions on bankruptcy rates in Italy during the initial phase of the pandemic. Using a national dataset of Italian firms and employing interrupted-time-series analysis, we find that bankruptcy rates declined significantly following the introduction of extensive economic support measures, including loan moratoria, guaranteed credit schemes, and direct grants. Our results suggest that these interventions mitigated liquidity constraints and prevented the immediate insolvency of firms, averting a sharp rise in bankruptcies despite severe economic contractions. However, we also highlight potential concerns regarding the postponement of insolvencies, contributing to the "zombification" of non-viable firms. The findings provide critical insights for policymakers regarding the balance between short-term economic stabilization and long-term market efficiency in crisis management.
Keywords: E65; G33; H12; 330; Bankruptcy; COVID-19; Government interventions; Interrupted-time-series